Signifikansi MaqÃ¢sid al-SharÃ®âah sebagai Kerangka Berpikir Epistemik Ijtihad - Sanuri, Sanuri (ISLAMICA: Jurnal Studi Keislaman, 2014)
This paper focuses on the importance of maqÃ¢sid al-sharÃ®âah for the effectiveness of ijtihad in Islamic law. The emergence of controversies at the beginning of the tenth century AD on the issue of the closing of the gate of ijtihÃ¢d has resulted in the rigidity of Islamic law and its methodological framework. Along with these issues, some contemporary scholars on maqÃ¢sid agreed that sharÃ®âah law (al-QurâÃ¢n) consists of partial (juzâÃ®yÃ¢t) and universal values (kullÃ®yyÃ¢t) that should be understood through a holistic approach in the frameworks of maqÃ¢sid. Shift in the meaning and orientation of maqÃ¢sid al-sharÃ®âah in some contemporary Muslim scholarsâ views, involving social sciences, philosophy of law, principles of morality, universality, social justice, human dignity, human rights, is a concrete manifestation of how Islamic law is able to provide answers to the current problems faced by the Muslim and non-Muslims community. This awareness has made contemporary Muslim thinkers strive to bring Islamic law into various achievements of progress in many aspects of life by emphasizing the importance of maqÃ¢sid al-sharÃ®âah.